2020
DOI: 10.1002/ppul.24626
|View full text |Cite
|
Sign up to set email alerts
|

The burden and risks of pediatric pneumonia in Nigeria: A desk‐based review of existing literature and data

Abstract: Background: Pneumonia is a leading killer of children under-5 years, with a high burden in Nigeria. We aimed to quantify the regional burden and risks of pediatric pneumonia in Nigeria, and specifically the states of Lagos and Jigawa.Methods: We conducted a scoping literature search for studies of pneumonia morbidity and mortality in under-5 children in Nigeria from 10th December 2018 to 26th April 2019, searching: Cochrane, PubMed, and Web of Science. We included grey literature from stakeholders' websites an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…In northern Nigeria, pneumonia case numbers are typically higher in the dusty Harmattan season (particularly the cooler, drier Jan-Feb period) and in the peak of the wet season (August), 40 although data regarding this is mixed. 6 Our data reflects this pattern, with higher pneumonia numbers and incidence in January that later months ( online supplemental appendix 6 ). While we do not expect our findings to have varied substantially with a longer sampling frame, climatic and other contextual factors make our prevalence estimates more relevant to other semirural contexts in the lower Saharan region of Africa.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In northern Nigeria, pneumonia case numbers are typically higher in the dusty Harmattan season (particularly the cooler, drier Jan-Feb period) and in the peak of the wet season (August), 40 although data regarding this is mixed. 6 Our data reflects this pattern, with higher pneumonia numbers and incidence in January that later months ( online supplemental appendix 6 ). While we do not expect our findings to have varied substantially with a longer sampling frame, climatic and other contextual factors make our prevalence estimates more relevant to other semirural contexts in the lower Saharan region of Africa.…”
Section: Discussionsupporting
confidence: 69%
“…We found few associations between sociodemographic factors and pneumonia or malnutrition, and no association with socioeconomic factors we might be expected (eg, crowding or lower socioeconomic status)—similar to previous analysis of 2018 DHS data. 6 We did not explore maternal factors and had fewer children from the poorest compounds, so may be missing key sociodemographic relationships. An interesting finding was the association between malnutrition and subsistence farming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pediatric pneumonia, which often occurs in infants and young children, is caused by the physiological and anatomical characteristics of the respiratory system, namely, narrow trachea and bronchial lumen, small number of pulmonary alveoli, easy blockage by mucus, and other features of children [ 12 , 13 ], combined with the fact that the autoimmune defense system of children is not yet developed and is prone to infection and other symptoms, the disease condition will progress rapidly and critically. Conventional Western medicine has great side effects, of which antibiotics are commonly applied to treat pneumonia, but with the yearly expansion of its application range, the pathogen resistance has increased, leading to more and more unsatisfactory therapeutic effects [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…From November 2018 to June 2019, we conducted a situational analysis of paediatric pneumonia in Lagos and Jigawa states of Nigeria, to inform the design of an intervention programme to reduce paediatric mortality. We found that while protective and preventive factors, such as vaccine coverage and clean cooking fuel, were high in Lagos, care-seeking and health facility service readiness were poor 3–6. Therefore, taking an approach that targets improved quality of care for pneumonia diagnosis and treatment could achieve mortality impact.…”
Section: Introductionmentioning
confidence: 92%